2021
DOI: 10.3390/ijms22157876
|View full text |Cite
|
Sign up to set email alerts
|

Males and Females Have Distinct Molecular Events in the Articular Cartilage during Knee Osteoarthritis

Abstract: Osteoarthritis (OA) is a major public health challenge that imposes a remarkable burden on the affected individuals and the healthcare system. Based on the clinical observation, males and females have different prevalence rates and severity levels of OA. Thus, sex-based differences may play essential roles in OA’s prognosis and treatment outcomes. To date, the comprehensive understanding of the relationship between sex and OA is still largely lacking. In the current study, we analyzed a published transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…For the six marker genes previously identified, we found that CDKN1A, FOSB, STMN2, and SLC2A3 genes were reported to be associated with cartilage inflammation in OA (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). For example, the expression level of CDKN1A will increase correspondingly during cartilage degeneration (44), IL-17 and IL-1beta induced collagenase-3 production through AP-1 occurred with differential protein complex, and stimulation resulted in FOSB activation (52), STMN2 has significant differences between preserved and subchondral bone (48).…”
Section: Discussionmentioning
confidence: 90%
“…For the six marker genes previously identified, we found that CDKN1A, FOSB, STMN2, and SLC2A3 genes were reported to be associated with cartilage inflammation in OA (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). For example, the expression level of CDKN1A will increase correspondingly during cartilage degeneration (44), IL-17 and IL-1beta induced collagenase-3 production through AP-1 occurred with differential protein complex, and stimulation resulted in FOSB activation (52), STMN2 has significant differences between preserved and subchondral bone (48).…”
Section: Discussionmentioning
confidence: 90%
“…The hyaline cartilage of the involved joint is still considered the major target for clinical and molecular research in humans. A recent study conducted by Li et al [ 15 ] demonstrated that cartilage has different gene expression between males and females, even in healthy joints: for example, TSIX transcript and XIST antisense RNA ( TSIX ) expression are significantly higher in females, although their function in the articular microenvironment is still under investigation. Moreover, most of the genes linked to OA onset are more involved in extracellular matrix turnover in females than in males.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, FOXO -mediated transcription factors are elevated in females’ osteoarthritic joints [ 34 , 64 , 65 ]. Conversely, in males, the PERK-ATF4-CHOP axis seems to be more involved in cartilage degeneration [ 15 , 66 ]. Male cartilage has also a lower expression of IGFAL , which encodes for a protein binding IGFs and increasing its half-life: therefore, the IGF-1 pathway seems to be less activated in males than in females [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations